Keterbatasan saran dan prasarana KETERBATASAN SARANA DAN PRASARANA DI LEMBAGA PAUD TK KARYA BUNDA MANDIRI - Wiwin kristiani Waruwu Wiwin (Universitas PGRI Palembang, 2023)
ABSTRACT In education, facilities and infrastructure are very important because they are needed. Educational facilities and infrastructure can be used to support the implementation of the teaching and learning process, either directly or indirectly in an institution in order to achieve educational goals. Educational facilities and infrastructure are a resource that is used as a benchmark for school quality and needs to be continuously improved in line with the development of sophisticated science and technology. The purpose of this study was to determine the limitations of facilities and infrastructure in PAUD Management at KARYA BUNDA MANDIRI Kindergarten. Data collection methods are through observation and interviews. The subject of this research is the principal of Karya Bunda Mandiri Kindergarten. The results of this study indicate that there are still deficiencies in the procurement of facilities and infrastructure at the Karya Bunda Mandiri Kindergarten school, Jalan Veterinary Main, Tembung. This is due to limited land resulting in a lack of existing space facilities. Keywords: Management of facilities and infrastructure in early childhood education.